A review of treatments targeting DNA-repair gene defects in metastatic castration resistant prostate cancer - Maslov, Diana V.; Sember, Quinne; Cham, Jason; Bhangoo, Munveer (Frontiers in Oncology, 2023)
Prostate cancer is the most common cancer in men. About 6% of those diagnosed will develop metastatic disease. Unfortunately, metastatic prostate cancer is fatal. Prostate cancer can be castration sensitive or castration resistant. Many treatments have been shown to improve progression free survival and overall survival in metastatic castration resistant prostate cancer (CRPC). In recent years, studies have been exploring targeting mutations in the DNA Damage Repair (DDR) response that may amplify oncogenes. In this paper, we aim to discuss DDR, new approved targeted therapies, and the most recent clinical trials in the setting of metastatic CRPC.